Trypanosoma cruzi Induces Regulatory B Cell Alterations in Patients With Chronic Chagas Disease - Girard, Magalí Celeste (2021)
The clinical evolution of patients with chronic Chagas disease (CCD) is mainly associated with an excessive inflammation and a defective immunomodulatory profile caused by the interaction between T. cruzi and the host. Regulatory B (Breg) cells exert immune suppression mostly through IL-10 production (B10 cells), but also through IL-10-independent mechanisms. Previously, we demonstrated that CCD patients with cardiomyopathy show changes in the ex vivo Breg cell phenotypic distribution although maintain IL-10 production capacity. Here, we sought to identify potential alterations on Breg cells upon in vitro stimulation. Isolated B cells from CCD patients with or without cardiomyopathy and non-infected (NI) donors were stimulated with T. cruzi lysate or CpG + CD40L, and characterized by flow cytometry based on the expression of CD24, CD27, CD38, and the regulatory molecules IL-10 and PD-L1. IL-10 and IL-17 secretion in the supernatant of B cells was evaluated by ELISA. Data showed that T. cruzi stimulation diminished the expression of CD24 and CD38 on CD27− B cells while reducing the percentage of CD24high inside CD27+ B cells. Furthermore, T. cruzi induced a regulatory B cell phenotype by increasing B10 cells and IL-10 secretion in all the groups. The innate-like B10 cells expansion observed in patients with cardiomyopathy would be associated with CD27− B10 cell subsets, while no predominant phenotype was found in the other groups. Patients with cardiomyopathy also displayed higher IL-17 secretion levels in T. cruzi–activated B cells. CpG + CD40L stimulation revealed that B cells from CCD patients and NI donors had the same ability to differentiate into B10 cells and secrete IL-10 in vitro. Additionally, CCD patients showed an increased frequency of CD24−CD27− B cells and a reduction in the percentage of CD24highCD27+ Breg cells, which appeared to be inversely correlated with the presence of T. cruzi DNA in blood. Finally, CCD patients exhibited a higher frequency of PD-L1+ B cells in T. cruzi–stimulated samples, suggesting that IL-10-independent mechanisms could also be tangled in the control of inflammation. Altogether, our results provide evidence about the potential role of Breg cells in the immune response developed against T. cruzi and its contribution to chronic Chagas cardiomyopathy.